Condensed Tannin Effects on Nitrogen Digestion in Ruminants: A Meta-analysis from in Vitro and in Vivo Studies - A Jayanegara; E Palupi (Faculty of Animal Science, Bogor Agricultural University, 2010)
Statistical meta-analysis approach was conducted to quantify the effect of a wide range of dietary condensed tannin (CT) concentration on nitrogen digestion in ruminants. A total of 19 studies from published papers and own previously unpublished studies comprising of 100 treatments were pooled in a database. The database was segregated into two categories based on different methods or systems where the experiments were carried out, i.e. in vitro (6 studies, 65 treatments) and in vivo experiments (13 studies, 35 treatments). Mixed model effects were applied to the data; different studies were treated as random effects whereas dietary CT (continuous predictor variable) was treated as fixed effects. The results showed that in the in vitro studies, organic matter digestibility (OMD) decreased linearly (P=0.002) as CT concentration in feed increased. Likewise, such linear decrease of OMD at increasing CT was observed in the in vivo studies (P < 0.001) as well as crude protein digestibility (CPD, P < 0.001). The variation on in vitro OMD was higher at lower level of CT. Nitrogen retention was not significantly affected by CT level. It was concluded that CT reduced nutrient digestibility in ruminants, but its effect on N retention was unclear from the present study.